Developing cassava's potential - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The food and income demands of the Philippines' growing population has led its government to pay particular attention to cassava. This crop was singled out because of its high yield potential, its adaptability to differing production systems and its...